2015
DOI: 10.1249/jsr.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Common Shoulder Injuries in American Football Athletes

Abstract: American football is a collision sport played by athletes at high speeds. Despite the padding and conditioning in these athletes, the shoulder is a vulnerable joint, and injuries to the shoulder girdle are common at all levels of competitive football. Some of the most common injuries in these athletes include anterior and posterior glenohumeral instability, acromioclavicular pathology (including separation, osteolysis, and osteoarthritis), rotator cuff pathology (including contusions, partial thickness, and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…Shoulder injuries are the fourth most common musculoskeletal football injury. 1,4,8,12,14,16,21 Kaplan et al 16 found that of the 336 collegiate football players invited to the 2004 NFL Combine, 50% had a history of shoulder injury and 33% of shoulder surgery. More specifically, it was found that shoulder injuries resulting in surgery are more common among football linemen.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder injuries are the fourth most common musculoskeletal football injury. 1,4,8,12,14,16,21 Kaplan et al 16 found that of the 336 collegiate football players invited to the 2004 NFL Combine, 50% had a history of shoulder injury and 33% of shoulder surgery. More specifically, it was found that shoulder injuries resulting in surgery are more common among football linemen.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentation of injuries to the rotator cuff can vary by type of injury and mechanism of onset. A thorough history that includes mechanism of injury and arm position at the time of injury can help the clinician determine the presence of injury to the rotator cuff [16]. Examination of the athlete should include thorough palpation and assessment of both active and passive range of motion.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Shoulder injury incidence rates are high in adolescents and young adults6; which are age groups likely to be active in sports. Existing data on shoulder sports injuries refer either to a limited subset of shoulder diagnoses,7–10 or all types of shoulder injuries limited to a specific sport 11–13. Shoulder sports injuries are also included in large population-based registry studies,1 14 15 but there are to our knowledge no previous studies on acute sports injuries to the shoulder including all shoulder trauma diagnoses and age groups in a general population cohort.…”
Section: Introductionmentioning
confidence: 99%